In-situ generated Mn3O4-reduced graphene oxide nanocomposite for oxygen reduction reaction and isolated reduced graphene oxide for supercapacitor applications - Jha, Plawan Kumar; Kashyap, Varchaswal; Gupta, Kriti; Kumar, Vikash; Debnath, Anil Krishna; Roy, Debashree; Rana, Shammi; Kurungot, Sreekumar; Ballav, Nirmalya (Carbon, 2019)
We have generated in situ nanocomposite of Mn3O4 and reduced graphene oxide (rGO) upon employing wet-chemical reduction of graphene oxide (GO) by Mn(II) salt as mild-reducing agent for the first time and examined the oxygen reduction reaction (ORR) activity in 0.1 M KOH electrolyte. The half-wave potential (E-1/2) of the nanocomposite catalyst (20% Mn3O4-rGO/C) was found to be around -0.153 V which is only similar to 87 mV negative from the commercially available catalyst (20% Pt/C). Remarkably, after 5000 linear sweep voltammetry cycles the E-1/2 shifted marginally by 20 mV; and the number of electrons transferred during ORR was estimated to be close to 4. Such an efficient electrocatalytic performance of the nanocomposite was primarily attributed to the synergistic interaction between Mn3O4 and rGO. The fabricated all-solid-state supercapacitor of rGO (extracted from the nanocomposite) in aqueous polyvinyl alcohol-sulfuric acid (PVA-H2SO4) gel polymer electrolyte (GPE) showed C-s value of similar to 310 F/g at a current density of 1 A/g along with long durability (10,000 charge-discharge cycles). All-solid-state flexible rGO supercapacitor exhibited high-flexibility and excellent durability (30,000 cycles with 100% retention of C-s). Our results provide an enormous opportunity in designing transition metal oxides decorated semiconducting reduced graphene oxide nanocomposite platforms for various electrochemical applications. (C) 2019 Elsevier Ltd. All rights reserved.

Seed-mediated growth of Pt on high-index faceted Au nanocrystals: the ag lining and implications for electrocatalysis - Roy, Debashree; Rajendra, Ranguwar; Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar; Ballav, Nirmalya (ACS Applied Nano Materials, 2021)
Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag+) which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. `While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag+ translates into a thicker Pt shell, in the present study, contradictory observations were made. In the presence of lower amounts of Ag+, thick Pt shells were visualized, while at higher concentrations of Ag+, the extent of Pt deposition via the galvanic replacement reaction was reduced. Additionally, the presence of Ag was deemed necessary for the Pt deposition to take place, either in the form of an underpotential deposition layer on the Au NCs or by introducing Ag+ in the growth solution. We have demonstrated our findings on two different Au NCs enclosed with high-index facets, concave cuboid, and elongated tetrahexahedra, which mirror similar observations and provide generality to our claim. To the best of our knowledge, the time required for Pt deposition on the Au core in the present work is the least among the reported seed-mediated routes. Furthermore, this work, besides presenting a facile and general route for the amalgamation of catalytic and plasmonic properties in hybrid Pt-Au NCs, sheds light on the mechanistic aspects of Ag-assisted wet-chemical generation of bimetallic Au@Pt NCs. The overall electrocatalytic performance of our Au@Pt NCs toward the oxygen reduction reaction was realized to be impressive.
Keywords: bimetallic nanostructure; galvanic replacement reaction; high-index facet; oxygen reduction reaction; seed-mediated growth; underpotential deposition